Environmental determinants of Leptospirosis in urban setting: a systematic review - Nor Rumaizah Mohd Nordin,; Mohd Hasni Ja’afar,; Anis Afina Yusof,; Mohd Firdaus Mohd Radi,; Shahrul Azhar Md Hanif,; Qistina Mohd Ghazali,; Mohd Rohaizat Hassan, (Penerbit Universiti Kebangsaan Malaysia, 2024)
Leptospirosis is among the neglected infectious diseases with high infection rates and mortality. This disease is largely underreported and underdiagnosed, often difficult to extinguish from other diseases with similar presentation such as Dengue. It is high time for the shift in strategy towards prevention and control particularly with its high prevalence in impoverished urban communities. Thus we aim to systematically review existing literature on the environmental indicators contributing to the risk of getting Leptospirosis in urban settings which is paramount for effective prevention and control. A literature search was conducted in December 2021 using Web of Sciences, PubMed, Ovid, and Scopus online databases. Open-access articles produced between 2011 and 2021 were analysed, emphasizing the environmental indicators for Leptospirosis infection in urban settings. Eight articles met the inclusion benchmarks. The majority of the studies in this review were done specifically in urban slum communities while two studies in Columbia and Puerto Rico consist of the overall urban community. Only three studies assessed environmental indicators as a risk for leptospirosis by using a checklist adapted from published and validated guidelines by the Centre of Disease Control. Adaptation was done to assimilate the characteristics of the area of study. Geography Information System (GIS) was used in four studies to measure and map out the related environmental indicators. One study employ known and verified guidelines to measure environmental risk and produce a prediction score for severe leptospirosis and its discriminative capacity by employing c-statistics derived from the receiver operating characteristic (ROC) curve, sensitivity, and false positivity rates. Adapting to existing validated and published guidelines in future studies with predictive scoring together with GIS could produce standardized and solid results which then can be replicated in other countries, involving more types of premises other than households such as food premises. Thus, enhanced and focused preventative and control strategies for environmental factors can be undertaken, allowing policymakers to deploy scarce healthcare resources more effectively.